“Dosis de fertilización granulado a base de micro elementos en el cultivo de un ecotipo de tomate (lycopersicum esculentum mill.), en el distrito de Lamas- Región San Martín” - Mejia Diaz, Edwink Sadi (2015)
The present study aimed to evaluate and determine which dose Micromate Fortifieed Calcium affects the performance and economic benefits ecotype cultivation of tomato (Lycopersicon esculentum Mill.) Under the town of Lamas. The research was conducted on the grounds of the Fundo "The Pacific" owned by Mr. Jorge Luis Pelaez Rivera, politically located in the district of district, province of Lamas, San Martin Region. The statistical design of randomized complete block (RCBD) with three replications and five treatments was used. For analyzing the information obtained SPSS19 Statistical Software, which determines significant differences through a P-P value <0.01 and P <0.05 analysis of variance (ANOVA) and the Duncan test was used with a P <0.05 probability. The treatments were: T1 (25 kg ha- 1), T2 (50 kg ha-1), T3 (75 kg ha-1),· T4 (100 kg ha-1) and TO Micromate Calcium Fortifieed (Witness). The variables evaluated were: plant height (cm), number of flower clusters, number of flowers I cluster, fruit diameter (cm), fruit length (cm), fruit weight per plant per treatment, economic analysis. The results indicate that the dose of 100 kg ha-1 Micromate Calcium Fortifieed (MCF) (T4) was the determining doses influenced the increase in yield (9708.66 kg ha-1) and higher benefit I cost ( 1.29), resulting in increased net profit of S l. 2082.35 soles respectively ecotype cultivation of tomato (Lycopersicum esculentum Mill.), Held in the town of Lamas. Keywords: ecotype, tomato, dosage, treatment, Calcium Micromate fortifieed, incidence, performance, economic benefit.